Community Service at Galerie Kirana On-Line Shop: Pengabdian kepada Masyarakat pada Galerie Kirana On-Line Shop - Veronika Nugraheni Sri Lestari; Reza Andriansyah; Nurmawati, Nurmawati; Subekti, Subekti (Universitas Lancang Kuning, 2024)
Online shopping has now become a modern trend that is enjoyed by most people, because it is able to attract and tempt every community, especially women. Because shopping cannot be separated from women, there are almost no women who do not like shopping. One of the media that is often used by online business people is Instagram social media.